Performance Of A Vapour Compression Refrigeration System Using Different Concentrations Of Go Nanolubricants And A Safe Charge Of R600a Refrigerant - Patil, Pradip Kailas; Dewangan, Rishi; Wagh, Hemant Krishnarao (Migration Letters, 2024)
Energy consumption is a major issue in vapour compression refrigeration systems. In many commercial and residential applications, the cooling system now consumes a significant amount of energy. Therefore, there is an immediate need to improve cooling systems’ energy efficiency. This study created three distinct samples of graphene-oxide nanolubricant with concentrations of 0.1, 0.3, and 0.5 g/L by dissolving the nanoparticles in polyolester (POE) oil. Then tests were conducted using the nanolubricant concentrations in 30, 40, and 50 g of R600a (isobutane) refrigerant, respectively. The outcomes were contrasted with the polyolester (POE) oil, which functioned as the primary lubricating substance. According to the results, a 40-g mass charge of R600a in 0.3 g/L graphene-oxide nanolubricant exhibits the greatest performance, with a maximum refrigeration effect of 0.197719 Kw, the highest coefficient of performance (COP) of 1.72, and the system’s lowest power consumption of 0.115 Kw. As a consequence, pure polyolester (POE) oil may be replaced with graphene-oxide nanolubricant in the vapour compression system.